HUMANISASI PENDIDIKAN DAN PENGEMBANGAN KETERAMPILAN MENGATASI KONFLIK - Darmiyati Zuchdi (LPMPP Universitas Negeri Yogyakarta, 2004)
Educational institutions have the responsibility ofdesigning apro gramto help individuals become society members ofsufficient intelli gence and praiseworthy character. These two criteria make it pos sible to bring about an ideal social life colored with a spirit ofdevel oping the self-potential to achieve prosperity and happiness in the world and in the hereafter. An educational system suitable for the development of a society ofindividuals with such intelligence and character is one which is humanistic in nature, treating the educational participant as an indi vidual as well as a member ofthe community who needs to be helped and encouraged in order to have effective habits based on an inte gration ofknowledge, skills, and will. Such an integration makes it possible for an individual or a community to leave a condition ofde pendence and move to that ofself-dependence and interdependence. Interdependence is extremely important in modern society because a more complex life can only be handled collaboJ;1ltively. Itmeans that skills ofestablishing hannonious relationships are needed and skills of resolving conflicts are among those which should be mastered well though they are not easy to master. In relation to the Indonesian con text, any conflict resolution skill is really important for everybody to have in order to be able to manage various conflicts coming to exist ence in society. Such humanization ofeducation should as soon as possible be the mission ofevery level ofeducational institution in Indonesia in order that basic values for achieving success are really put in the foun dations ofthe character building ofthe nation. Among those values are integrity, modesty, loyalty, courage, fairness, honesty, patience, industriousness, politeness, and consistency. Key words: humanization ofeducation, effective habits, conflict resolution skills.